PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE TS-TS (TWO STAY TWO STRAY) SEBAGAI UPAYA UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI KELAS X AK 1 SMK PGRI WONOASRI TAHUN PELAJARAN 2011/2012 - Moh Ubaidillah; Supri Wahyudi Utomo; Juli Murwani (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
The purpose of this research is to improve the activity, student learning outcomes, and the correlation between the activities of the learning outcomes of students of class X Ak 1 after learning implemented using cooperative learning type TS TS (two stay two stray) at SMK PGRI Wonoasri. This research is the study participants. The population used in this study were students of class X SMK PGRI Wonoasri by the number of 102 students. The number of samples taken by 51 students of class X AK 1. The collection of the necessaries data in this study were obtained through the method of observation, methods of testing, and documentation. Analysis of the data used to analyze the research data is quantitative analysis techniques and different test (correlation). In action research, the researcher conducted two cycles in a single class. Each cycle performed by the procedure of planning, action, observation and reflection. The data was collected using a questionnaire sheet activity and test questions. Sheet activity questionnaire to determine activity of students during learning activities, while about a test conducted at the end of each cycle of learning that is used to determine student learning outcomes.